Biology and Environment: Proceedings of the Royal Irish Academy (JSTOR)
Biology and Environment is a broad-spectrum journal publishing biological and environmental research on topics of Irish interest for an international readership. The journal should be essential reading for those researchers concerned with these disciplines on the island of Ireland.
Keywords: Irish Studies